Analisis Kebijakan Anggaran Pemerintah Daerah Pada Masa Pandemi dalam Memulihkan Perekonomian Kota Jambi - Azna Yusra Sylviana; Hendri Koeswara; Roni Ekha Putera (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
This research aimed to finding out how government of Jambi city's implying the budget policy throughout the pandemic era by using qualitative method. The data of this research were collected through study of literature and documentations that are related to budget policy of Jambi city, as for the samples this research use purposive sampling that is determined by articles on the internet. The result shows that there are some updates of the policy made by Jambi city's government in 2019 to keep the econimc stable in the midle of the pandemic and one of those update is an improvement of coordination between regional and regency government to ensure that the internal control of regional revenue management runs effectively in order to prevent the occurrence of irregularities in the expenditure of funds. With the new policy government expecting there will be an increasement of regional taxes and levy revenue. Due to the pandemic that is happening now government has been suffering several economical issues such as an decreasement of regional income as the effect of the decline in the income of the citizen Jambi city. As the result of the fund reduction, deduction of funds on the levy results as much as more than the initial amount of the funds then followed by local taxes that is reducing by a third of the initial amount. The governance of Jambi city also had been done refocusing the budget allocation fund just like what the central government told to in order to support government programs in this pandemic era.